STUDENTS’ PERCEPTION OF THE USE OF BUZZ GROUP TEHCNIQUE IN TEACHING READING COMPREHENSION AT THE NINETH GRADE OF SMP N 1 TANJUANG BARU - Febriza, Tesa; Safitri, Loli; Martini (JEE (Journal of English Education), 2022)
This research was aimed to find out about students’ perception of the use of buzz group technique to teach reading comprehension. The problems were related to students’ reading comprehension. This research used descriptive quantitative to describe students’ perception about using a buzz group in teaching reading comprehension. The population was all of 9th grade of SMP N 1 Tanjuang Baru. To take the sample, the researcher used total technique sampling, because the population less than 100 students. The sample of this research was 48 students. The researcher used a questionnaire to collect data and used Total Score/ Y X 100% to analyze the data. The result of this research showed that the students had good perception of the use buzz group technique in teaching reading.